A Systematic Review of Approaches for Continuous Quality Improvement Capacity-Building. Issue 2 (13th March 2022) - Loper, Audrey C.; Jensen, Todd M.; Farley, Amanda B.; Morgan, Jenille D.; Metz, Allison J.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Context: Continuous quality improvement (CQI) has become prominent in public health settings; yet, little consolidated guidance exists for building CQI capacity of community-based organizations. Objective: To synthesize relevant literature to identify guiding principles and core components critical to building the capacity of organizations to adopt and use CQI. Design: We employed a systematic review approach to assess guiding principles and core components for CQI capacity-building as outlined in the literature. Eligibility Criteria: Studies meeting the following criteria were eligible for review: (1) empirical, peer-reviewed journal article, evaluation study, review, or systematic review; (2) published in 2010 or later; and (3) capacity-building activities were described in enough detail to be replicable. Studies not including human subjects, published in a language other than English, or for which full text was not available were excluded. Study Selection: The initial return of records included 6557 articles, of which 1455 were duplicates. The research team single-screened titles and abstracts of 5102 studies, resulting in the exclusion of 4842 studies. Two hundred sixty-two studies were double-screened during full-text review, yielding a final sample of 61 studies from which data were extracted. Main Outcome Measures: Outcome measures of interest were operationalized descriptions of guiding principles and core components of the CQI capacity-building approach. Results: Results yielded articles from medical education, health care, and public health settings. Findings included guiding principles and core components of CQI capacity-building identified in current practice, as well as infrastructural and contextual elements needed to build CQI capacity. Conclusions: This consolidation of guiding principles and core components for CQI capacity-building is valuable for public health and related workforces. Despite the uneven distribution of articles from health care, medical education, and public health settings, our findings can be used to guide public health organizations in building CQI capacity in a well-informed, systematic manner.